EDXRF tra analisi e imaging : Nuovi intriganti sviluppi nella diagnostica de i Beni Culturali - Gigante, Giovanni Ettore; Barcellos Lins, Sergio A. (Archeomatica, 2023)
The essay resume the most recent history of EDXRF, a nondestructive X-Ray fluorescence microanalysis of pigments of paintings used by the help of elemental colour Map and Portable Instrumentation Package: the innovative Implementations employed in the past years in the high resolution of imaging till the perfetto simulation.